2015
DOI: 10.1371/journal.pone.0126706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing of Korean Familial Hypercholesterolemia Using Whole-Exome Sequencing

Abstract: Familial hypercholesterolemia (FH) is a genetic disorder with an increased risk of early-onset coronary artery disease. Although some clinically diagnosed FH cases are caused by mutations in LDLR, APOB, or PCSK9, mutation detection rates and profiles can vary across ethnic groups. In this study, we aimed to provide insight into the spectrum of FH-causing mutations in Koreans. Among 136 patients referred for FH, 69 who met Simon Broome criteria with definite family history were enrolled. By whole-exome sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
(36 reference statements)
2
24
1
2
Order By: Relevance
“…In the study, LDLR point mutations were most frequent on exons 4 and 14 ( Fig. 1) 5, 18) . Point mutations of LDLR have been previously reported in a variety of gene locations in Koreans 19) .…”
Section: Genetic Characteristicsmentioning
confidence: 73%
See 2 more Smart Citations
“…In the study, LDLR point mutations were most frequent on exons 4 and 14 ( Fig. 1) 5, 18) . Point mutations of LDLR have been previously reported in a variety of gene locations in Koreans 19) .…”
Section: Genetic Characteristicsmentioning
confidence: 73%
“…Point mutations of LDLR have been previously reported in a variety of gene locations in Koreans 19) . Large deletions [20][21][22][23] and copy number variation 18) in LDLR associated with FH have also been identified. Although not common, mutations in APOB and PCSK9 are reported in Korean FH patients 5,18) .…”
Section: Genetic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from 97 Korean FH patients revealed conventional clinical criteria (Simon Broome or Dutch Lipid Clinic) showed limited mutation detection power (35% -37%), but the mutation detection rate by MEDPED criteria was as high as 67% -75%, and the best LDL-C threshold for putative mutations in LDLR, APOB or PCSK9 genes was 225 mg/dl (5.8 mmol/L) in this group of patients 30) . However, whole-exome sequencing analysis did not identify any other novel genes accounting for the genetic cause of FH 31) . Our initial genetic testing was only performed in those probands with severe phenotypes and their family members and this may contribute to the high detection rate (100% after excluding the case with sitosterolemia).…”
Section: Genetic Testing In Familial Hypercholesterolemia Patients Wimentioning
confidence: 86%
“…first used whole-genome resequencing to perform a genetic diagnosis in an 11-month-old female with severe hypercholesterolemia and found that the patient carried two nonsense mutations in the ABCG5 gene14. Since then, whole exome sequencing has been used to detect mutations in FH patients, but this technology has not yet found any FH-causing mutations in genes other than LDLR, APOB or PCSK91516. Target exome sequencing in combination with clinical criteria now has a high success rate in the genetic diagnosis of FH patients with hyperlipidemia8171819.…”
Section: Discussionmentioning
confidence: 99%